Application of high-strength biodegradable polyurethanes containing different ratios of biobased isomannide and poly (ϵ-caprolactone) diol. (May 2013) - Lim, Dong-In; Park, Hyung-Seok; Park, Jeong-Hui; Knowles, Jonathan C; Gong, Myoung-Seon
Biodegradable–biocompatible polyurethanes were prepared with fixed hexamethylene diisocyanate and varying ratios of isomannide and poly(ϵ-caprolactone) diol using a simple one-step polymerization without a catalyst. The polyurethane structures were confirmed by 1 H-nuclear magnetic resonance, Fourier transform infrared spectroscopy, and gel permeation chromatography. The glass transition temperatures were determined by thermal analysis to be between 25°C and 30°C. Degradation tests performed at 37°C in phosphate buffer produced mass losses of 5%–10% after 8 weeks. After 5 days of culture, using osteoblastic cells, the relative cell number on all the polyurethane films was only slightly lower than that of an optimized tissue culture plastic. These polymers offer significant promise with a simplistic synthesis and controlled degradation.